Substitution of Linoleic Acid for Other Macronutrients and the Risk of Ischemic Stroke. Issue 12 (December 2017) - Venø, Stine K.; Schmidt, Erik B.; Jakobsen, Marianne U.; Lundbye-Christensen, Søren; Bach, Flemming W.; Overvad, Kim
Abstract : Background and Purpose—: Ischemic stroke is a major health problem worldwide, but the influence of dietary factors on stroke risk is not well known. This study aimed to investigate the risk of ischemic stroke and its subtypes with a higher intake from linoleic acid and a concomitant lower intake from saturated fatty acids, monounsaturated fatty acids, or glycemic carbohydrates. Methods—: In the Danish prospective Diet, Cancer, and Health Study of 57 053 participants aged 50 to 64 years at baseline, information on diet was collected using a validated semiquantitative food frequency questionnaire. Information on ischemic stroke was obtained from the Danish National Patient Register, and cases were all validated and subclassified according to the TOAST (Trial of ORG 10172 in Acute Stroke Treatment) classification. Substitution of linoleic acid for saturated fatty acid, monounsaturated fatty acid, or glycemic carbohydrates was investigated in relation to the risk of ischemic stroke and subtypes. Cox proportional hazards regression was used to estimate the associations with ischemic stroke adjusting for appropriate confounders. Results—: During 13.5 years of follow-up 1879 participants developed ischemic stroke. A slightly lower risk of ischemic stroke was found with a 5% higher intake of linoleic acid and a concomitant lower intake of saturated fatty acid (hazard ratio, 0.98; 95% confidence interval, 0.83–1.16), monounsaturated fatty acid (hazard ratio, 0.80; 95% confidence interval, 0.63–1.02), and glycemic carbohydrates (hazard ratio, 0.92; 95% confidence interval, 0.78–1.09), although not statistically significant. Similar patterns of association were found for large-artery atherosclerosis and small-vessel occlusions. Conclusions—: This study suggests that replacing saturated fatty acid, glycemic carbohydrate, or monounsaturated fatty acid with linoleic acid may be associated with a lower risk of ischemic stroke.